Selective Hydrosilylation of Esters to Aldehydes Catalysed by Iridium(III) Metallacycles through Trapping of Transient Silyl Cations. Issue 39 (18th August 2016) - Corre, Yann; Rysak, Vincent; Capet, Frédéric; Djukic, Jean‐Pierre; Agbossou‐Niedercorn, Francine; Michon, Christophe
Abstract: The combination of an iridium(III) metallacycle and 1, 3, 5‐trimethoxybenzene catalyses rapidly and selectively the reduction of esters to aldehydes at room temperature with high yields through hydrosilylation followed by hydrolysis. The ester reduction involves the trapping of transient silyl cations by the 1, 3, 5‐trimethoxybenzene co‐catalyst, supposedly by formation of an arenium intermediate whose role was addressed by DFT calculations. Abstract : Winning combination : A combination of an Ir III metallacycle and 1, 3, 5‐trimethoxybenzene provides efficient catalysis of the hydrosilylation of esters to aldehydes (see figure). By using triethylsilane and a further hydrolysis step, the reactions proceed rapidly with high yields and selectivities under mild conditions. The trapping of transient silyl cations was performed for the first time and studied by DFT calculations.